2009
DOI: 10.1158/1078-0432.ccr-08-2365
|View full text |Cite
|
Sign up to set email alerts
|

PCI-24781 Induces Caspase and Reactive Oxygen Species–Dependent Apoptosis Through NF-κB Mechanisms and Is Synergistic with Bortezomib in Lymphoma Cells

Abstract: Purpose: We investigated the cytotoxicity and mechanisms of cell death of the broadspectrum histone deacetylase (HDAC) inhibitor PCI-24781, alone and combined with bortezomib in Hodgkin lymphoma and non-Hodgkin lymphoma cell lines and primary lymphoproliferative (CLL/SLL) cells. Experimental Design: Apoptosis, mitochondrial membrane potential, cell cycle analysis, and reactive oxygen species (ROS) were measured by flow cytometry, whereas caspase activation was determined by Western blot. Nuclear factor κB (NF-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 38 publications
7
74
0
Order By: Relevance
“…The synergistic induction of apoptosis after HDACi/ BTZ treatments has been partially associated with an inhibition of NF-kB signaling in mature B-cell malignancies, myeloid leukemia, and T-ALL (9,10,13,16). These observations are consistent with the finding that NF-kB signaling is indispensable for the homeostasis of mature B cells and contributes to the survival of mature B-cell malignancies (17,18).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The synergistic induction of apoptosis after HDACi/ BTZ treatments has been partially associated with an inhibition of NF-kB signaling in mature B-cell malignancies, myeloid leukemia, and T-ALL (9,10,13,16). These observations are consistent with the finding that NF-kB signaling is indispensable for the homeostasis of mature B cells and contributes to the survival of mature B-cell malignancies (17,18).…”
Section: Introductionsupporting
confidence: 85%
“…Proteasome inhibitors such as bortezomib (BTZ) were found to increase substantially the activity of HDACi in different hematologic and solid malignancies (9)(10)(11)(12)(13). To date, no systematic studies have been conducted to analyze the response of B-cell precursor leukemias to HDACi/proteasome inhibitor combinations.…”
Section: Introductionmentioning
confidence: 99%
“…3E). NK-kB activation and mitochondrial membrane potential were shown to be closely associated with ROS generation (31,32). However, according to our results, no significant change in expression of NFkB-related proteins, including p-p65, p65, and IKKa/b, was observed after treatment with combined bortezomib/SAHA when compared with either drug alone (Fig.…”
Section: Resultssupporting
confidence: 50%
“…[39][40][41][42] Recent clinical trials combining bortezomib and the HDAC inhibitor vorinostat showed a promising outcome in relapsed and refractory MM, including activity among some patients with prior exposure to bortezomib. 43 Another study showed that vorinostat adds to the antitumor activity of the proteasome inhibitor carfilzomib in human diffuse large B-cell lymphoma (DLBCL) cells.…”
Section: Combined Treatment With Onx 0912 and Bortezomib Dex Lenalimentioning
confidence: 99%